The A-B transition in superfluid helium-3 under confinement in a thin slab geometry - N. Zhelev (Nature Portfolio, 2017)
Superfluid helium-3 provides a clean testing ground for the understanding of quantum phases and their transitions. Here the authors show that when helium is confined in a nanofluidic cavity supercooling across the first-order A–B transition is suppressed, indicating an intrinsic nucleation mechanism.